The Mystery of magnets - Berger, Melvin ([New York] : Newbridge Communications, 1995)
Learn the characteristics and uses of magnets from a compass to a giant industrial magnet. Poles and magnetic fields are also introduced and explained.
Includes index.
K-3.
Keywords: Magnetism; Magnets; Oversize books -- Specimens; Big books; Magnetism; Magnets